Empowerment of Kader Kesehatan Jiwa in Overcoming Psychosocial Problems Through Support of Mental Health and Psychosocial Pandemic Covid-19 - Dwi Heppy Rochmawati; Betie Febriana; Wahyu Endang Setyowati (Indonesian Journal of Global Health Research, 2022)
Bandarharjo, North Semarang District, Central Java Province is a village that already has a Kader Kesehatan Jiwa (KKJ). A total of 56 peoples have been confirmed positive for COVID-19 and require treatment at the hospital because they experience moderate to severe symptoms. Some peoples who were confirmed positive with mild symptoms underwent independent treatment at home, during the pandemic which is still ongoing. Objective of this study was to improve the abilities and skills of Kader Kesehatan Jiwa in promoting mental and psychosocial health, preventing mental health and psychosocial problems, and detecting and recovering mental health and psychosocial problems due to the COVID-19 pandemic. The research program for independent learning policies on independent campuses and community service based on research results and prototype PTS DITJEN DIKTIRISTEK is carried out by empowering Kader Kesehatan Jiwa (KKJ) by providing training and assistance in implementing Mental Health and Psychosocial Support for the COVID-19 pandemic (MHPSS) to Kader Kesehatan Jiwa (KKJ). Results 60 respondents, after being given mental health and psychosocial support for 3 days and assistance for 8 days, their physical health condition increased to 75% which was initially 3.3%. This study uses a descriptive study and observation method, the conditions obtained are mental health conditions from 35% to 55%, mental emotional disorders from 28.4% decreased to 16.7%, hallucinations remained 11.6% and post-traumatic disease syndrome rates decreased from 25% to 16.7%. Conclusion Mental Health and Psychosocial Support reduces the respondent's physical and mental health problems.